The diagnostic value of endoscopic score based on acetic acid-enhanced narrow-band imaging for gastric intestinal metaplasia - Chen XU; Zhengyang LI; Haiyan WANG; Yuhao WANG; Xuanguang YE; Miao JIANG (Zhongguo Linchuang Yixue, 2025)
ObjectiveTo explore the diagnostic value of endoscopic grading of gastric intestinal metaplasia (EGGIM) score under acetic acid-enhanced narrow band imaging (AA-NBI) observation mode for gastric intestinal metaplasia (GIM). MethodsA total of 120 patients who underwent gastroscopy at Jinshan Hospital of Fudan University from February 2022 to February 2023 were selected. All patients underwent both white light and AA-NBI endoscopy, with photographic records of intestinal metaplasia in five areas: greater curvature of antrum, lesser curvature of antrum, greater curvature of corpus, lesser curvature of corpus and incisura. EGGIM score was performed: 0 for no intestinal metaplasia, 1 point for focal intestinal metaplasia (GIM area ratio≤30%), 2 points for extensive intestinal metaplasia (GIM area ratio＞30%), with a total score of 10 points. Targeted biopsies were performed on suspicious GIM lesions found during endoscopy. If no suspicious GIM lesions were observed, random biopsies were performed according to the updated Sydney system. The pathological histological examination results were staged based on the operative link on gastric intestinal metaplasia assessment (OLGIM) system. The diagnostic value of EGGIM score for OLGIM stage Ⅲ-Ⅳ patients was evaluated using receiver operating characteristic (ROC) curves. ResultsThe sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of AA-NBI in detecting GIM were 96.3%, 91.6%, 94.5%, 95.0%, and 93.6%, respectively. The area under the ROC curve for EGGIM diagnosing OLGIM stage Ⅲ-Ⅳ was 0.952 (95%CI 0.914-0.990). The optimal cut-off value for EGGIM was 5 points, with a sensitivity of 96.7% (95%CI 87.6%-99.4%) and specificity of 88.1% (95%CI 76.5%-94.7%). ConclusionsEGGIM score (≥5 points) under AA-NBI mode has good diagnostic capability for patients with OLGIM stage Ⅲ-Ⅳ.